2012
DOI: 10.1007/s00381-012-1952-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cerebrovascular reactivity using real-time BOLD fMRI in children with moyamoya disease: a pilot study

Abstract: rtCVR assessment in children with moyamoya disease is feasible, and the results are comparable to that of standard off-line analysis. The results from off-line analysis are only available, at the earliest, several hours after the MRI has been completed. rtCVR can overcome this difficulty and may be equally reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The difficulty in administering CO 2 challenges and concerns regarding the repeatability of CO 2 paradigms may be responsible for the limited implementation in clinical scenarios. Breath-hold paradigms have been administered successfully to paediatric patients with moyamoya disease (Thomas et al, 2013), suggesting that even patient groups that are notoriously difficult to scan can successfully complete breath-hold challenges in the MR scanning environment. The results presented in the current study indicate that poor performance of breath-hold challenges is not necessarily a limiting factor in robust mapping of CVR in patients; the End-tidal CO 2 analysis method compensates for ability and consistency factors and provides repeatable CVR values despite these performance variations.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in administering CO 2 challenges and concerns regarding the repeatability of CO 2 paradigms may be responsible for the limited implementation in clinical scenarios. Breath-hold paradigms have been administered successfully to paediatric patients with moyamoya disease (Thomas et al, 2013), suggesting that even patient groups that are notoriously difficult to scan can successfully complete breath-hold challenges in the MR scanning environment. The results presented in the current study indicate that poor performance of breath-hold challenges is not necessarily a limiting factor in robust mapping of CVR in patients; the End-tidal CO 2 analysis method compensates for ability and consistency factors and provides repeatable CVR values despite these performance variations.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that the increased MTT correlated well with the decreased CVR in patients with occlusive cerebrovascular disease[41,42]. According to these studies, MMT and TTP should be predictive parameters of PWI for assessing reduced CVR, which have been evaluated based on the principle of BOLD signal fluctuations in patients with MMD[35,36,37,38,39]. In the present study, there was no correlation between frontal lobe ALFF and CBV or CBF.…”
Section: Discussionmentioning
confidence: 98%
“…[34] As the disease progresses, more blood flows towards areas of the brain capable of decreasing vascular resistance in response to a vasodilatory stimulus (the steal phenomenon), which could in turn cause a decrease in BOLD signals in the areas of the brain where vascular resistance was already minimized. [35,36,37,38,39] Compared with the NC group, the CVR in the bilateral hemispheres of patients were impaired to varying degrees, which may have reduced the resting-state BOLD responses. Therefore, we speculate that the reduced frontal lobe ALFF may be related to the abnormal cerebral perfusion in patients with MMD.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach for the assessment of CVR is the breath-hold technique[20]. Thomas et al[16] used a breath-hold challenge in eight consecutive pediatric moyamoya patients and found that while all breath-hold challenge during general anesthesia resulted in best quality CVR maps, only 42% of studies without general anesthesia yielded best quality CVR maps. Finally, a previous study Shiino et al[18] validated CO 2 BOLD CVR against acetazolamide SPECT CVR in 17 healthy subjects and 10 patients with severe ICA steno-occlusive disease, including 2 patients with moyamoya disease.…”
Section: Discussionmentioning
confidence: 99%
“…This sample size should however be considered in light of the very low prevalence of moyamoya syndrome of 3/1000000 in European countries[3]. Consequently, the previous related studies discussed above include 8[16], 11[12], 12[13] and 13 pediatric[15] patients with moyamoya. It is also important to note that the vasodilation induced by acetazolamide is stronger than the vasodilation induced by the inhalation of CO 2 via a simple nasal cannula.…”
Section: Discussionmentioning
confidence: 99%